Perencanaan Kolam Stabilisasi Untuk Penanganan Air Lindi (Leachate) Pada Calon Tempat Pembuangan Akhir (TPA) Kabupaten Mesuji - Ismadi Raharjo; Suprapto Suprapto; Iskandar Zulkarnain (Jurusan Teknologi Pertanian, 2013)
Land sites of Final Processing Disposal (TPA) Mesuji district has a relative flat topographic with a 3,20 ha area, the extents of the allocation of land use is planned landfill area 2.60 ha and the remaining 0.60 ha as area supporting infrastructure. From the analysis of the water balance in landfill sites was obtained percolation 39 mm/month, with an area of landfill area of 2.60 ha planned then be generated leachate (leachate) that must be managed as much as 33.2 m3/day. Leachate treatment plan using stabilization pond method consisting of an anaerobic pond with a detention time of 12 days and an 398.40 m3 capacity will reduce pollutants leachate influent BOD around 1500 mg/lt be 288.46 mg/lt; Facultative pond with a detention time of 8 days and a capacity of 265.60 m3 pond will reduce pollutants leachate influent BOD 288.24 mg/lt be 79.51 mg/lt, and Maturasipond with a detention of 10 days and a capacity of 322 m3 pond will reduce the material influent BOD of leachate pollutant 79.51 mg/lt be 16.86 mg/lt is further eligible to flow into water bodies (rivers). The texture of the soil conditions in the local area is clay, then structural stabilization pond construction recommended using reinforced concrete plate. Keywords: Leachate, BOD, Sstabilization Pond, Detention Time, Capacity Pond